All but the Rarest of Children: Miller and Montgomery's Implicit Ban on Victim and Community Impact Testimony in Juvenile Life Without Parole Sentencing - Allison M. Scoggin (Washington University Journal of Law & Policy, 2020)
In Miller v. Alabama and Montgomery v. Louisiana, the Supreme Court held mandatory juvenile life without parole sentences unconstitutional and applied this retroactively. Many state juvenile life without parole statutes list factors for a court to consider in deciding whether to sentence to life without parole. Frequently, victim or community impact testimony (or both) are included. This Note argues that the inclusion of such should not be permitted during the consideration of a juvenile life without parole sentence, as it does not contribute to individualized sentencing or rehabilitative potential of an offender.
Keywords: Miller v. Alabama; Montgomery v. Louisiana; juvenile; life without parole; parole; victim testimony; community impact testimony